2009
DOI: 10.1055/s-0029-1216808
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis of Tetraalkyl 2,3,4,5-Thiophenetetracarboxylate Derivatives

Abstract: A facile and direct synthetic entry to tetraalkyl 2,3,4,5-thiophenetetracarboxylate derivatives is described. This involves the reaction of dialkyl acetylenedicarboxylates with elemental sulfur in the presence of triethyl phosphite or an N-heteroaromatic compound such as isoquinoline, 1-methyl-1H-imidazole, or pyridine as catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…To our delight, pyridinium 1d bearing a methoxyl group exhibited the best reactivity and furnished the highest yield of 81 % within only 1 h. Then, we adjusted the ratio of reactants, but no better results were obtained. In addition, we also examined a series of common solvents including ethyl acetate, acetone, toluene, and so on (entries [8][9][10][11][12][13][14]. All of them could support the reaction, but only moderate yields were delivered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our delight, pyridinium 1d bearing a methoxyl group exhibited the best reactivity and furnished the highest yield of 81 % within only 1 h. Then, we adjusted the ratio of reactants, but no better results were obtained. In addition, we also examined a series of common solvents including ethyl acetate, acetone, toluene, and so on (entries [8][9][10][11][12][13][14]. All of them could support the reaction, but only moderate yields were delivered.…”
Section: Resultsmentioning
confidence: 99%
“…The solid organosulfur compounds are air‐stable, odorless, easy‐ to‐ handle, and readily available. Alizadeh had proposed these thiolates were the key intermediates in the synthesis of tetraalkyl 2,3,4,5‐thiophenetetracarboxylate, but this kind of pyridinium 1,4‐zwitterionic thiolates have not yet been recognized as useful and versatile synthons ever since their emergence, to the best of our knowledge. In this context, intrigued by their unique structures, we envisaged that the reactive intermediates could be used to prepare sulfur‐containing heterocycles via two reaction modes: [5+m, path a], with pyridine as a reactive moiety, and [3+m, path b], with pyridine as a leaving group (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the reaction of alleneoate 132 and electron-poor alkene 133 in the presence of P(NMe 2 ) 3 catalyst produces 98% yield of 134, whereas in the presence of (4-ClC 6 H 4 ) 3 P as catalyst leads to 92% yield of isomeric cyclohexene 135 (Scheme 59B) [377]. Related to the Rauhut-Currier reaction is the formal (4+1)-cycloaddition of sulfur (S 8 ) with two equivalents of acetylenedicarboxylic esters producing tetraalkyl thiophene-2,3,4,5-tetracarboxylate, a reaction catalyzed by nucleophilic bases such as triethyl phosphite, isoquinoline, pyridine, and N-methylimidazole [378]. An example of catalytic enantioselective intermolecular cross-Rauhut-Currier reaction is given in Scheme 59C [379].…”
Section: The Rauhut-currier Reactionmentioning
confidence: 99%
“…sulfur (S8) with two equivalents of acetylenedicarboxylic esters producing tetraalkyl thiophene-2,3,4,5-tetracarboxylate, a reaction catalyzed by nucleophilic bases such as triethyl phosphite, isoquinoline, pyridine, and N-methylimidazole [378]. An example of catalytic enantioselective intermolecular cross-Rauhut-Currier reaction is given in Scheme 59C [379].…”
Section: The Morita-baylis-hillman Reactionmentioning
confidence: 99%
“…[9][10][11][12][13] Very recently, Alizadeh et al reported the reaction of acetylenic esters and elemental sulfur in the presence of catalytic amount of N-heterocycle leading to the formation of thiophenetetracarboxylates (Scheme 1). 14 We found that when this reaction is carrying out in the presence of pyridine as the third reagent, not as a catalyst, thiophenetetracarboxylates are not obtained but the stable 1,4-diionic organosulfur compounds are produced (Scheme 1).…”
mentioning
confidence: 99%